Encapsulation of collagenase within biomimetically mineralized metal-organic frameworks: designing biocomposites to prevent collagen degradation - Bim Júnior, Odair [UNESP]; Bedran-Russo, Ana; Flor, Jader B. S. [UNESP]; Borges, Ana F. S.; Ximenes, Valdecir F. [UNESP]; Frem, Regina C. G. [UNESP]; Lisboa-Filho, Paulo N. [UNESP] (Royal Society of Chemistry (RSC), 2019)
A growing class of multifunctional porous materials termed metal-organic frameworks (MOFs) has attracted attention for immobilization of biomolecules via self-assembly of inorganic and organic building blocks. Herein, we report the rapid formation of MOF shells surrounding collagen-degrading enzymes by using a biomimetic mineralization approach. Bacterial collagenase, which is functionally related to endogenous proteases in the human body, was used as a nucleating agent to induce the mineralization of zeolitic imidazolate framework-8 (ZIF-8) as a crystalline shell. This zinc-based MOF material was selected due to its remarkable stability under physiological conditions and good biocompatibility. The straightforward, water-based synthesis yielded microporous collagenase-embedded ZIF-8 particles. Once immobilized inside the biomimetically mineralized MOF, the protease presented limited catalytic activity, being ineffective in the proteolysis of a collagen-like peptide. In conclusion, biomimetic mineralization of ZIF-8 using collagenase not only provided immobilization of the enzyme, but also enabled the control of its activity. This synthetic approach provides a potentially useful concept in the prevention of proteolytic activity involved in the degradation of collagen matrices in living organisms.